About the legend of Alexandria: Epiphanius, De mensuris et ponderibus, cap. 9 - Luca Tiberi (Bibliothecae.it, 2019)
A new interpretation of a passage of Epiphanius’ De mensuris et ponderibus, chapter 9 is proposed. Considering the text resulting from the manuscript tradition and from the corrections made by the editors of Epiphanius, we gain two conclusions: 1) the text of the older codices Vaticani is not correct for the sense; 2) the better text of a group of later codices, that is satisfying for the sense and for the grammar, was misunderstood by some editors, producing a wrong interpretation of the whole passage: the king Ptolemy Philadelphus knew from Demetrius Phalereus that existed a people, ancestor of the Romans, called Latins by the Greeks of the early III century b.C. If this is true, the king may have been in search of the Latins’ books for his library.